Settlement of Bad Credit with Guarantee of Unregistered Land Rights (Case Study Number 52/Pdt.G/2021/PN Mjk) - Frida Maulida Rahardjo; Sri Astutik (Fakultas Hukum Dehasen, 2023)
This study aims to find out how to settle bad loans with collateral for land rights that are not registered (study of decision number 52/Pdt.G/2021/PN.Mjk), as well as explain the legal consequences of bad credit agreements with guaranteed land rights that are not registered ( Study of Decision Number 52/Pdt.G/2021/PN Mjk) and how to solve it. The approach method used by the author in this study is normative, according to the results of research on the relationship between borrowing and repayment of debt, the possibility of unexpected events by the debtor cannot be ignored. When a borrower faces difficulties in paying off credit, financial institutions, such as banks, take steps to deal with it with the aim of giving the borrower an opportunity to fulfill his obligations. These actions may involve restructuring payment schedules, adjusting terms, and rearranging. Humans fulfill their life needs by interacting with other humans. Interactions that are often carried out are by making agreements. Many types of agreements are made, including: sale - purchase agreements, lease agreements, accounts payable agreements. In the current era, the Indonesian economy is progressing and the needs of each individual are increasing. Therefore, many individuals, if they cannot make ends meet using their own money, will carry out debts. Good for individuals, savings and loan cooperatives, loans to banks, and others.